Mitochondrial genome and its regulator TFAM modulates head and neck tumourigenesis through intracellular metabolic reprogramming and activation of oncogenic effectors - Hsieh, Yi-Ta; Tu, Hsi-Feng; Yang, Muh-Hwa; Chen, Yi-Fen; Lan, Xiang-Yun; Huang, Chien-Ling; Chen, Hsin-Ming; Li, Wan-Chun (Cell death & disease, 2021)
Mitochondrial transcriptional factor A (TFAM) acts as a key regulatory to control mitochondrial DNA (mtDNA); the impact of TFAM and mtDNA in modulating carcinogenesis is controversial. Current study aims to define TFAM mediated regulations in head and neck cancer (HNC). Multifaceted analyses in HNC cells genetically manipulated for TFAM were performed. Clinical associations of TFAM and mtDNA encoded Electron Transport Chain (ETC) genes in regulating HNC tumourigenesis were also examined in HNC specimens. At cellular level, TFAM silencing led to an enhanced cell growth, motility and chemoresistance whereas enforced TFAM expression significantly reversed these phenotypic changes. These TFAM mediated cellular changes resulted from (1) metabolic reprogramming by directing metabolism towards aerobic glycolysis, based on the detection of less respiratory capacity in accompany with greater lactate production; and/or (2) enhanced ERK1/2-Akt-mTORC-S6 signalling activity in response to TFAM induced mtDNA perturbance. Clinical impacts of TFAM and mtDNA were further defined in carcinogen-induced mouse tongue cancer and clinical human HNC tissues; as the results showed that TFAM and mtDNA expression were significantly dropped in tumour compared with their normal counterparts and negatively correlated with disease progression. Collectively, our data uncovered a tumour-suppressing role of TFAM and mtDNA in determining HNC oncogenicity and potentially paved the way for development of TFAM/mtDNA based scheme for HNC diagnosis.